TRANSDUCERS 2007 - 2007 International Solid-State Sensors, Actuators and Microsystems Conference 2007
DOI: 10.1109/sensor.2007.4300348
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Si DRIE on Vibratory MEMS Gyroscope Performance

Abstract: Today angular rate sensors (gyroscopes) for automotive application are fabricated by a silicon surface micromachining process (SMM). One critical performance parameter of these micromachined vibratory gyroscopes is the mechanical coupling between the drive and sense mode due to manufacturing imperfections. Excessive coupling, called quadrature error, leads to large zero rate output (ZRO or QBias). This paper discusses for the first time, the dependence between quadrature error and profile asymmetries in releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 2 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Later on Lam Research, one of the big Californian plasma etch equipment suppliers, reported about successful low quadrature development activities on 150 mm wafers together with Fraunhofer Institute ISIT, Germany on their TCP DSiE reactor with a flat coil plasma source. Customer demo runs on 150 mm substrates also turned out much lower quadrature values on Bosch gyroscope devices, being the decision point to invest into a Lam trench etch equipment for Bosch production site.…”
Section: The Vision Becomes Realitymentioning
confidence: 99%
“…Later on Lam Research, one of the big Californian plasma etch equipment suppliers, reported about successful low quadrature development activities on 150 mm wafers together with Fraunhofer Institute ISIT, Germany on their TCP DSiE reactor with a flat coil plasma source. Customer demo runs on 150 mm substrates also turned out much lower quadrature values on Bosch gyroscope devices, being the decision point to invest into a Lam trench etch equipment for Bosch production site.…”
Section: The Vision Becomes Realitymentioning
confidence: 99%
“…The mechanical unbalance which is coupling the primary and the secondary mode is due to a distortion of the rectangular shaped cross sections of the beam elements, in particular at the drive meanders. In the mathematical model derived below this effect will be accounted for by means of beam elements with rhomboid cross sections characterized by the so-called side wall angle n, see Merz et al (2007). All electrostatic actuators are assumed to be voltage controlled with a desired input voltage, see, e.g., Seeger and Boser (2003).…”
Section: Principle Of Operationmentioning
confidence: 99%
“…Indeed, on most of the MEMS gyroscope designs, one or several springs are place symmetrically on each corner of the resonator so that if all of the springs are identical, the resulting coupling stiffness is null [ 30 ]. However, if there is geometrical dispersion of the flexure springs, especially width variation as it is a critical dimension for the springs, the resulting coupling stiffness would not be equal to zero [ 37 ], which would generate a quadrature force. To our knowledge, few investigations have been carried out about the contributions of the geometrical dispersion of the springs on quadrature error.…”
Section: Introductionmentioning
confidence: 99%